Essence of Scalability in Wireless Sensor Network for Smart City Applications. Issue 1 (January 2021) - Dogra, Roopali; Rani, Shalli; Sharma, Bhisham; Verma, Sandeep
Abstract: Internet of Things (IoT) is the emerging research area. Along with many physical objects, Wireless Sensor Networks (WSNs) play an impeccable role in the smart city applications. It is learned from the retrospective study that the interaction between different types of objects, gathering of data from all the zones, their analyses etc., are very difficult to handle without energy conserving algorithms and protocols. Furthermore, applications of IoT specifically smart cities require a fault tolerant, scalable and reliable framework for real time processing of collected data. In this paper, we have proposed a cluster-based routing methodology which could be used at the sensing layer of smart city IoT. We select Cluster Head (CH) based on energy, distance, network energy and node density. The consideration of above parameters helps in acquiring the optimized performance of the protocol Zone-Stable Election Protocol (Z-SEP). We have performed simulations in MATLAB to emphasize the role of scalability of WSN in smart city application. We found that this protocol under performs when it is encountered for scalablity.